Hybrid simulation of a zipper-braced steel frame under earthquake excitation. - Yang, T. Y. (Earthquake engineering & structural dynamics.)
Hybrid simulation is a testing methodology that combines laboratory and analytical simulation to evaluate seismic response of complex structural framing systems. One or more portions of the structure, which may be difficult to model numerically or have properties that have not been examined before, are tested in one or more laboratories, whereas the remainder of the structure is modeled in software using one or more computers. These separate portions are assembled such that combined dynamic response of the hybrid model to excitation is computed using a time-stepping procedure. A hybrid simulation conducted to examine the seismic response of a type of steel concentrically braced frame, the suspended-zipper-braced frame, is presented. The hybrid simulation testing architecture, hybrid model, test setup, solution algorithm, and the seismic response of the suspended-zipper-braced frame hybrid model are discussed. Accuracy of this hybrid simulation is examined by comparing hybrid and computer-only simulations and the errors are quantified using an energy-based approach. This comparison indicates that the deployed hybrid simulation method can be used to accurately model the seismic response of a complex structural system such as the zipper-braced frame.